Analysis Of Factors Influencing The Application Of Financial Accounting Standards For Entities Without Public Accountability (Sak Etap) In Financial Reporting Of Cooperatives In Bogor City - Yuppy Trriwidatin Triwidatin; Abdullah (MultiTech Publisher, 2023)
Study This aim For know influencing factors _ application standard accountancy finance entity without accountability public . Factors the is level education part finance cooperative , age effort , socialization of SAK ETAP and understanding accounting . Population inside researcher This is whole cooperative active in Bogor City . Whereas For sample study are 83 cooperatives use purposive sampling method . Data analysis technique used in study This is analysis multiple linear regression . Research results show that level education part finance cooperative , age effort , socialization of SAK ETAP and understanding accountancy influential positive and significant in a manner simultaneous to implementation of SAK ETAP. For level education part finance cooperative influential positive in a manner Partial to application of SAK ETAP, meanwhile age business No influential positive and significant in a manner Partial to implementation of SAK ETAP, socialization of SAK ETAP has an effect positive and significant in a manner Partial to implementation of SAK ETAP and understanding accountancy influential positive and significant in a manner Partial to implementation of SAK ETAP.